Effect of Sowing Date on Growth and Yield of Different Carrot Varieties (Daucus carota L.) - Giri, D.; Srivastava, A.; Shrestha, A. K.; Raut, S. K.; Giri, H. N. (Journal of Tikapur Multiple Campus, 2024)
A study was conducted at Agriculture and Forestry University, Rampur, Chitwan, from October 2019 to March 2020 to evaluate the effect of sowing date on the growth and yield of four different carrots (Daucus carota L.) varieties. The experimental treatments were three different sowing dates (19th October, 13th November, and 8th December) and four varieties (New Kuroda, Nepa Dream, SK3, and Taki) which constituted 12 treatments. The experiment was set up using a randomized complete block design with three replications. The results revealed that sowing dates and varieties significantly influenced the growth and yield of carrots. But interaction effect was not significant. Maximum plant height, number of leaves per plant, leaf length, leaf breadth, canopy diameter, root length (15.37 cm), root diameter (2.74 cm), and fresh root weight (133 g) were obtained with Nepa Dream variety. Similarly, the highest plant height, number of leaves per plant, leaf breadth, canopy diameter, root diameter (3.27 cm), root length (16.23 cm), and fresh root weight (162.60 g) was obtained with first sowing (19th October) which might be due to favorable condition available during the growing condition and also early sowing possibly attributed to maximum photosynthesis with longer growth period than the later sowing. The combined effect of sowing date and varieties was significant with the number of leaves per plant, cortex diameter, and core-to-cortex ratio. So based on the results of the experiment, Nepa Dream sown on 19th October was economically better for the optimum yield and quality production in Chitwan, Nepal.